Assessment of Helminth contamination in wastewater and irrigated vegetables at Kawo Irrigation Farm, Kaduna State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
The research aimed to investigate the presence of Helminths on vegetables grown with confluence of untreated municipal and abattoir wastewater in the Kawo abattoir irrigation farm, Kaduna State, Nigeria. The wastewater sample was collected from four different points designated as WW01, WW02, WW03, and WW04. Vegetable samples were also collected from these points and labeled: SP01, SP02, SP03, and SP04 (spinach) and LT01, LT02, LT03, and LT04 (lettuce). The laboratory analysis of the samples was conducted using standard parasitological techniques, including macroscopy and microscopy, for Helminths in the wastewater and fresh vegetable produce. Ova of Fasciolopsis buski, Tania saginata, Cyst of Entamoeba histolytica and Ova of Ascaris lumbricoid were found and above the recommended guidelines, which specify
Keywords: Abattoir; Farmers; Health; Sample; Tapeworm